CHARACTER BUILDING MANAGEMENT WITH THE CONCEPT OF LOVE - Suryanti, Eny Wahyu; Widayanti, Febi Dwi (Universitas Brawijaya, Indonesia, 2018)
This study aims to determine the character building management with the concept of love in LPI Malang. The research method used is a qualitative method by using data collecting technique such as interview, observation, and documentation. Objects in this study are in LPI Malang. The conclusion that can be gained from this research is that the character building management in LPI Malang City uses the concept of loving 360 degree, covering love to Allah and Prophet, love of parent/ teacher, love fellow, love excellence, love self, love science and technology , love of the natural surroundings, the love of the nation and the country that is integrated in all learning activities in school.